The Protective Role of Immunomodulators on Tissue-Type Plasminogen Activator-Induced Hemorrhagic Transformation in Experimental Stroke: A Systematic Review and Meta-Analysis - Yang Ye; Yang Ye; Yu-Tian Zhu; Yu-Tian Zhu; Hong-Xuan Tong; Jing-Yan Han; Jing-Yan Han (Frontiers Media S.A., 2020)
Background: Recanalization with tissue plasminogen activator (tPA) is the only approved agent available for acute ischemic stroke. But delayed treatment of tPA may lead to lethal intracerebral hemorrhagic transformation (HT). Numerous studies have reported that immunomodulators have good efficacy on tPA-induced HT in ischemic stroke models. The benefits of immunomodulators on tPA-associated HT are not clearly defined. Here, we sought to conduct a systematic review and meta-analysis of preclinical studies to further evaluate the efficacy of immunomodulators.Methods: The PubMed, Web of Science, and Scopus electronic databases were searched for studies. Studies that reported the efficacy of immunomodulators on tPA-induced HT in animal models of stroke were included. Animals were divided into two groups: immunomodulators plus tPA (intervention group) or tPA alone (control group). The primary outcome was intracerebral hemorrhage, and the secondary outcomes included infarct volume and neurobehavioral score. Study quality was assessed by the checklist of CAMARADES. We used standardized mean difference (SMD) to assess the impact of interventions. Regression analysis and subgroup analysis were performed to identify potential sources of heterogeneity and evaluate the impact of the study characteristics. The evidence of publication bias was evaluated using trim and fill method and Egger's test.Results: We identified 22 studies that met our inclusion criteria involving 516 animals and 42 different comparisons. The median quality checklist score was seven of a possible 10 (interquartile range, 6-8). Immunomodulators improved cerebral hemorrhage (1.31 SMD, 1.09-1.52); infarct volume (1.35 SMD, 0.95-1.76), and neurobehavioral outcome (0.9 SMD, 0.67-1.13) in experimental stroke. Regression analysis and subgroup analysis indicated that control of temperature and time of assessment were important factors that influencing the efficacy of immunomodulators.Conclusion: Our findings suggested that immunomodulators had a favorable effect on tPA-associated intracerebral hemorrhage, cerebral infarction, and neurobehavioral impairments in animal models of ischemic stroke.